Optimizing Children's Emotional Literacy Through Fairy Tales with Emotional Self-Regulation - S Nailul Muna Aljamaliah Syifa; Yulianeta; Sumiyadi; Halimah; Dewi Kusuma; Vismaia S Damaianti (Bale Literasi: Lembaga Riset, Pelatihan & Edukasi, Sosial, Publikasi, 2026)
This research is motivated by the low attention paid to the development of emotional literacy in elementary school students in learning, which has so far been dominated by cognitive aspects. In fact, the ability to recognize, understand, and manage emotions is an important part of 21st-century competencies. The use of folklore as a learning medium rich in moral and emotional values has not been optimally developed in the form of interactive digital media integrated with an emotional self-regulation approach. This indicates a gap between the potential of learning resources based on local wisdom and the needs of modern learning. This study aims to develop a folklore-based flipbook media with an Emotional Self-Regulation approach and to test its feasibility and effectiveness in students' emotional literacy. The study used the Research and Development method with the ADDIE model which includes the stages of analysis, design, development, implementation, and evaluation. The research subjects were fourth-grade students of Trikarsa Elementary School, Bandung. Data collection techniques were carried out through expert validation, observation, interviews, questionnaires, and pretests and posttests. The results showed that the developed flipbook media received a very feasible category based on the assessment of media experts (97.08%) and material experts (82.3%), and was feasible according to literary experts (64.3%). The implementation results showed an increase in students' emotional literacy from 82.2% in the pretest to 90.7% in the posttest, a 9% increase. These findings confirm that folktale-based flipbooks with an Emotional Self-Regulation approach are effective in improving students' emotional literacy. The novelty of this research lies in the integration of digital interactive media, local wisdom, and an Emotional Self-Regulation approach in a single learning design. The implications of this research indicate that innovative media based on local culture can be an alternative strategy in supporting holistic learning in elementary schools.